Espacio y enunciación en la dinámica textual de la lengua española - José Luis Cifuentes Honrubia (Estudios de Lingüística, 1984)
This article, inscribed within the frame of Greimas-inspired Textual Semiotics, tries to explain how the linguistic space at work is one of the «setting to discourse mechanisms» for the semio-narrative structures, that is, one of the main mechanisms within the articulation of the utterance and enunciation, that fact already know by Greimas. The contribution we are try to do with this article consits of the demonstration that spatial locatives, in its deictic view as well the inherent one, form part of the so called token-reflexive expressions: a token-reflexive expression, as a type, has no particular meaning, but a signification that turns a particular meaning when the enunciation takes place in the context of a particular token for this expression; then, the signification of the type is completed by the token display, reflexing the fact of its own enunciation and moving to take into account the context it comes from. The spatial locatives —deictics and inherents— refer always to the situation of enunciation framing them, and they need it to determine their meaning. At the same time they articulate the dialectics utterance enunciation, they can be considered as mechanisms of textual coherence, though in this occasion the isotopy formed by them would always be asystematic, because it constantly need the situation of enunciation.